Assessing the impact of adaptations to the clinical workflow in radiotherapy using transit in vivo dosimetry. (January 2023) - Bossuyt, Evy; Nevens, Daan; Weytjens, Reinhilde; Taieb Mokaddem, Ahmed; Verellen, Dirk
Highlights: Analyzing in vivo dosimetry data can assist in continuous quality improvement. In vivo dosimetry data can be used to assess adaptations to the clinical workflow. Optimizing clinical workflows leads to enhanced in vivo dosimetry results. Large-scale in vivo dosimetry data can indicate general items for improvement. Abstract: Background and Purpose: Currently in-vivo dosimetry (IVD) is primarily used to identify individual patient errors in radiotherapy. This study investigated possible correlations of observed trends in transit IVD results, with adaptations to the clinical workflow, aiming to demonstrate the possibility of using the bulk data for continuous quality improvement. Materials and methods: In total 84, 100 transit IVD measurements were analyzed of all patients treated between 2018 and 2022, divided into four yearly periods. Failed measurements (FM) were divided per pathology and into four categories of causes of failure: technical, planning and positioning problems, and anatomic changes. Results: The number of FM due to patient related problems gradually decreased from 9.5% to 6.6%, 6.1% and 5.6% over the study period. FM attributed to positioning problems decreased from 10.0% to 4.9% in boost breast cancer patients after introduction of extra imaging, from 9.1% to 3.9% in Head&Neck patients following education of radiation therapists on positioning of patients' shoulders, from 6.1% to 2.8% in breast cancer patients after introduction of ultrahypofractionated breast radiotherapy with daily online pre-treatment imaging and from 11.2% to 4.3% in extremities following introduction of immobilization with calculated couch parameters and a Surface Guided Radiation Therapy solution. FM related to anatomic changes decreased from 10.2% to 4.0% in rectum patients and from 6.7% to 3.3% in prostate patients following more patient education from dieticians. Conclusions: Our study suggests that IVD can be a powerful tool to assess the impact of adaptations to the clinical workflow and its use for continuous quality improvement.